An Overview of Environmental Aspects in the Poetry of Mumtaz Athar (Environmental Critical Studies) - Ajmal, Shoaib; Tanveer, Sarwat (sourcecoder, 2023)
Eco-criticism is a theory that prioritizes life centralism over human centralism. This theory speaks of protecting the rights of other species. Mumtaz Athar is an Urdu poet from Multan. He has warned of environmental hazards in his poetry. Native plants, birds and river conservation have spoken of.For them, environmental protection should be protected from the dangers faced by trees and birds. He has taken a defiant approach in his poetry so that the reader can consider environmental issues.